Various Patterns of Unit Shift: an Indonesian-English Translation Study - Afrianto, Afrianto; Robai, Ahmad; Septiari, Fatma (Journal of Arts and Education, 2024)
This study investigates the concept of unit shift in the translation of a Bahasa Indonesia-English short story. The main objective is to identify and examine the different patterns of unit shifts in translation. In order to accomplish this goal, the researchers applied Catford's model of translation shift. Furthermore, the methodology employed for this research was qualitative to offer a comprehensive portrayal and understanding of the studied phenomenon. The data were originated from short stories composed in both Indonesian and English; Clara atawa Wanita Yang Diperkosa. After carefully comparing the translated materials, the researchers classified the data according to the unit shift patterns. These patterns include 1) bound morphemes to free morphemes, 2) free morphemes to bound morphemes, 3) words to phrases, 4) words to clauses, 5) words to sentences, 6) phrases to single words, and 7) phrases to clauses. It was observed that the most common type of shift identified was from single words to phrases. This occurrence could be due to the absence of a corresponding single word in the target language that fully conveys the meaning of the original source language and the translator took into account the aesthetic aspect of the text.